Development and Validation of Two Instruments Measuring Intrinsic, Extraneous, and Germane Cognitive Load - Klepsch, Melina; Schmitz, Florian; Seufert, Tina (Frontiers in Psychology, 2017)
Cognitive Load Theory is one of the most powerful research frameworks in educational research. Beside theoretical discussions about the conceptual parts of cognitive load, the main challenge within this framework is that there is still no measurement instrument for the different aspects of cognitive load, namely intrinsic, extraneous, and germane cognitive load. Hence, the goal of this paper is to develop a differentiated measurement of cognitive load. In study 1 (N = 97) we developed and analyzed two strategies to measure cognitive load in a differentiated way: (1) Informed rating: We trained learners in differentiating the concepts of cognitive load, so that they could rate them in an informed way. They were asked then to rate 24 different learning situations or learning materials related to either high or low intrinsic, extraneous, or germane load. (2) Naïve rating: For this type of rating of cognitive load we developed a questionnaire with 2-3 items for each type of load. With this questionnaire, the same learning situations had to be rated. In the second study (N = between 65 and 95 for each task) we improved the instrument for the naïve rating. For each study, we analyzed whether the instruments are reliable and valid, for study 1, we also checked for comparability of the two measurement strategies. In study 2 we conducted a simultaneous scenario based factor analysis. The informed rating seems to be a promising strategy to assess the different aspects of cognitive load, but it seems not economic and feasible for larger studies and a standardized training would be necessary. The improved version of the naïve rating turned out to be a useful, feasible, and reliable instrument. Ongoing studies analyze the conceptual validity of this measurement with up to now promising results.